Anesthesiologists' Preferences regarding Visitor Presence during Placement of Neuraxial Labor Analgesia. (20th May 2018) - Kumaraswami, Sangeeta; Pothula, Suryanarayana; Inchiosa, Mario Anthony; Kubal, Keshar Paul; Burns, Micah Alexander
Abstract : Introduction . Neuraxial labor analgesia has become an integral part of modern obstetric anesthetic practice. Presence of a familiar person during its placement may be beneficial to the patient. A survey was sent to anesthesiologists practicing obstetric anesthesia in the USA to determine their views. Methods . The survey queried the following: existence of a written policy; would they allow a visitor; visitor's view, sitting or standing; reasons to allow or not allow a visitor; and influence by other staff on the decision. The responses were analyzed using multiple chi-square analyses. Results . Most practitioners supported allowing a visitor during placement. Reduction of patient anxiety and fulfillment of patient request were the major reasons for allowing a visitor. Sitting position and no view of the workspace were preferred. Visitor interference and safety were cited as the major reasons for precluding a visitor. Nonanesthesia providers rarely influenced the decision. Epidural analgesia was the preferred technique. Essentially no bias was found in the responses; there was statistical uniformity regardless of procedures done per week, years in practice, professional certification, geographic region (rural, urban, or suburban), or academic, private, or government responders. Conclusion . The practice of visitor presence during the placement of neuraxial labor analgesia is gaining acceptance.